Defense training of border villages with passive defense approach; case study: border villages of Piranshahr - Mohammad Hassan Nami (مسکن و محیط روستا)
One of the adverse consequences of the country's development policies in the border areas is the rupture in the spatial structure, which reflects these policies in the form of disruption of the balance in the endogenous growth of settlements at different levels, disorder in the spatial system of human assemblies, and discontinuity in spatial relations and disorder in the economic, social, cultural, administrative, and physical function and finally geographical isolation and underdevelopment. A general overview shows the weak position of the border and marginal regions in comparison with the central regions of the country in the process of spatial development, comprehensive security, and social justice. The current research with the statistical community of rural settlements of Piranshahr county in West Azarbaijan province is of applied research, with a descriptive-analytical method, a systemic problem-solving approach and library-documentary and survey-field data collection. The study is based on rural development plans and emphasizes on the passive defense approach as a security-oriented and defense-based approach. The spatial findings were analyzed using GIS, the Analysis Hierarchy Process (AHP), and fuzzy logic. The results indicate that out of 147 villages of the county, more than 60 villages, which constitute to more than 40% of the population of rural areas, are very vulnerable. Also, the highest level of vulnerability is observed in the rural settlements of three western counties of Lahijan, Piran, and Western Mangoor which are border counties.